2000
DOI: 10.1002/(sici)1097-4547(20000515)60:4<495::aid-jnr8>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Pressure related apoptosis in neuronal cell lines

Abstract: Pressure is a crucial component of the cellular environment, and can lead to pathology if it varies beyond its normal range. The increased intra-ocular pressures in acute glaucoma are associated with the loss of neurons by apoptosis. Little is known regarding the interaction between pressure and apoptosis at the level of the cell. The model developed in this study examines the effects of elevated ambient hydrostatic pressure directly upon cultured neuronal lines. Conditions were selected to be within physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Previous studies in glaucoma have suggested that RGC and axonal loss may be determined by the level of IOP elevation, (14,22,25,30), with evidence that the extent of neuronal apoptosis induced in vitro is determined by the magnitude of the insult (21,29). We next investigated the size of stimulus correlated with the level of apoptosis in our models.…”
Section: Visualization Of Single Nerve Cell Apoptosis In Vivomentioning
confidence: 96%
“…Previous studies in glaucoma have suggested that RGC and axonal loss may be determined by the level of IOP elevation, (14,22,25,30), with evidence that the extent of neuronal apoptosis induced in vitro is determined by the magnitude of the insult (21,29). We next investigated the size of stimulus correlated with the level of apoptosis in our models.…”
Section: Visualization Of Single Nerve Cell Apoptosis In Vivomentioning
confidence: 96%
“…The desired gas mix can be pressurized to a constant ambient hydrostatic pressure ranging from 0 to 200 mmHg (28). We applied pressure chamber to visualize directly the infl uence of pressure on the viability, motility, morphology, DNA integrity and sperm fertilizing ability with functional-morphological view.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure chamber used in this study is an established model that allows a gas mix pressurized to a constant ambient hydrostatic pressure ranging from 0-200±2.25 mmHg over the pressure period (28). After pressurization, pressure was restored to atmospheric, and the culture plates removed from the pressure chamber for analysis.…”
Section: Hydrostatic Pressure Treatmentmentioning
confidence: 99%
“…The unpressurized control cell groups were treated identically within a chamber, but with no pressure applied. The cell culture pressure chamber used in this study is an established model (Agar et al, 2000;Agar et al, 2006) that allows a gas mix to be pressurized to a constant ambient hydrostatic pressure ranging from 0-200 ± 2.25 mmHg over the pressure period. After pressurization, the pressure was restored to the atmospheric value, and the culture plates were removed from the pressure chamber for analysis.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Namely biological and pharmacological techniques (1), mechanical cues (2), and external mechanical and electrical forces (3) have been used to regulate mMSCs differentiation (Titushkin et al, 2010). Brown (2000) suggested that a significant factor in nerve regeneration is the mechanical environment.…”
Section: Introductionmentioning
confidence: 99%